2016
DOI: 10.1111/peps.12183
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Safety: A Meta‐Analytic Review and Extension

Abstract: Although psychological safety research has flourished in recent years, and despite the empirical support for the important role of psychological safety in the workplace, several critical questions remain. In order to address these questions, we aggregate theoretical and empirical works, and draw on 136 independent samples representing over 22,000 individuals and nearly 5,000 groups, to conduct a comprehensive meta‐analysis on the antecedents and outcomes of psychological safety. We not only present the nomolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
622
1
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 599 publications
(679 citation statements)
references
References 206 publications
(186 reference statements)
36
622
1
20
Order By: Relevance
“…Hofstede (2001) predicts that individuals from higher UA cultures seek greater security and stability in their professional careers and therefore tend to have longer job tenure and less turnover intention (see also Debus, Probst, König, & Kleinmann, 2012;García-Cabrera, & García-Soto, 2011;Staufenbiel & König, 2010). In a similar vein, Frazier, Fainshmidt, Klinger, Pezeshkan, and Vracheva (2017) also found that work design characteristics and supportive work contexts showed significantly stronger effects on psychological safety in high UA cultures. Furthermore, examining participation in decision-making and organisational commitment, Singh, Bhagat, and Mohanty (2011) empirically supported a moderating impact of UA on the participation-affective commitment relationship.…”
Section: Cultural Values and Their Impact On Jd-r Theorymentioning
confidence: 94%
“…Hofstede (2001) predicts that individuals from higher UA cultures seek greater security and stability in their professional careers and therefore tend to have longer job tenure and less turnover intention (see also Debus, Probst, König, & Kleinmann, 2012;García-Cabrera, & García-Soto, 2011;Staufenbiel & König, 2010). In a similar vein, Frazier, Fainshmidt, Klinger, Pezeshkan, and Vracheva (2017) also found that work design characteristics and supportive work contexts showed significantly stronger effects on psychological safety in high UA cultures. Furthermore, examining participation in decision-making and organisational commitment, Singh, Bhagat, and Mohanty (2011) empirically supported a moderating impact of UA on the participation-affective commitment relationship.…”
Section: Cultural Values and Their Impact On Jd-r Theorymentioning
confidence: 94%
“…As job resources are typically drawn from the organisation and interpersonal relations that stimulate personal growth, learning and development (Bakker and Demerouti, 2007), HPWSs create a supportive work environment that makes it easy for employees to discharge any insecurities and anxieties (Edmondson, 1999;Nembhard and Edmondson, 2006). A metaanalysis by Frazier et al (2017) reveals that autonomy, interdependence, role clarity, leader relations and supportive work context are all significant and positive predictors of psychological safety; all of which are core components of HPWSs. Employee skills and knowledge are valued, and problem-solving is used to resolve mistakes, consequently leading to increases in employee psychological safety (Edmondson, 1999).…”
Section: High-performance Work Systems and Psychological Safetymentioning
confidence: 99%
“…Therefore, a work environment that it is safe to take interpersonal risks and express new ideas is critical for follower creativity, because the environment can motivate and increase one’s willing to show creativity (Carmeli et al, 2010). Specifically, in a psychologically safe environment, they are more likely to take risks and express new ideas because the perception of safe climate allows them to overcome the anxiety and fear of failure (Frazier et al, 2016). In contrast, in a psychologically unsafe environment, they are more likely to develop defensive orientation and are less likely to show creativity at work (West and Richter, 2008).…”
Section: Theory and Hypothesesmentioning
confidence: 99%